Implementasi Program Pemeliharaan Penyandang Masalah Kesejahteraan Sosial Anak (Studi Kasus UPTD Kampung Anak Negeri Wonorejo) - Anisah Puteri Djatmiko; Yusuf Hariyoko; Adi Soesiantoro (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
In implementing public policy for the care of children with social welfare problems (PMKS), it is necessary to plan strategically the reasons for the background of the initial problem of cases of violence against children. The city of Surabaya was selected as the highest population in East java, amounting to 595 children. Ratified by mayor regulation Number 61 of 2012 concerning organization of the technical implementation unit for the State Children’s village Service at the Surabaya City Social Service, PMKS maintenance is carried out with the acceptance process action (1) Contoling by Satpol PP (2) delegeted to the Pondok Social Keputih neighborhood, (3) identification data from the results of the raid on children with social problems in the city of Surabaya from information from related institutions (RT/RW/Lurah) from community members (4) acceptance and maintenance with physical and social environmental assessment officers UPTD and regulations that must obeyed. The objectives of this research are (1) to obtain research results from the successful implementation of the program (2)to obtain a collection of data representing the implementation of the program. The research method is qualitative research and theory by George C.Edward III.